2018
DOI: 10.1002/jcb.27022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fucoxanthin on autophagy and apoptosis in SGC‐7901cells and the mechanism

Abstract: Autophagy and apoptosis are involved in the development of a variety of cancers. Fucoxanthin is a natural compound known to have antitumor effects, so we aimed to explore its effects on autophagy and apoptosis in gastric cancer SGC7901 cells. Specifically, we performed methyl thiazolyl tetrazolium assay, transmission electron microscopy, real-time polymerase chain reaction, Western blot analysis, immunofluorescence assay, and cell apoptosis analysis to clarify the role of fucoxanthin in SGC-7901 cells. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 31 publications
(63 reference statements)
1
19
0
Order By: Relevance
“…The data obtained in the present study suggested that vortioxetine inactivated the PI3K/AKT pathway by decreasing the phosphorylation levels of AKT and mTOR, as well as cyclin D1. Indeed, correlations have been demonstrated between apoptosis and autophagy; for example, the promotion of autophagy could enhance the apoptosis of GC cells [45,46]. Hence, we speculated that vortioxetine induced apoptosis and autophagy via activation of the PI3K/AKT pathway in GC cells.…”
Section: Discussionmentioning
confidence: 90%
“…The data obtained in the present study suggested that vortioxetine inactivated the PI3K/AKT pathway by decreasing the phosphorylation levels of AKT and mTOR, as well as cyclin D1. Indeed, correlations have been demonstrated between apoptosis and autophagy; for example, the promotion of autophagy could enhance the apoptosis of GC cells [45,46]. Hence, we speculated that vortioxetine induced apoptosis and autophagy via activation of the PI3K/AKT pathway in GC cells.…”
Section: Discussionmentioning
confidence: 90%
“…The same pro-apoptotic effect caspase-mediated was also observed in human bladder cancer cells, in human cervical cancer cells HeLa [216]; in human breast cancer cells MCF-7 and in estrogen-resistant cells MDA-MB-231 [204]. In gastric cancer SGC-7901 cells, fucoxanthin induced autophagy, which in turn promoted apoptosis with caspase-3 cleavage and Bcl-2 downregulation [217]. There is some evidence showing that fucoxanthin could be used to potentiate the action of conventional anticancer drugs.…”
Section: Marine-derived Compounds: Inductors Of Apoptosismentioning
confidence: 76%
“…The results pointed out the importance of a combination drug therapy approach within cancer research [ 149 ]. Moreover, fucoxanthin inhibited viability, induced autophagy and apoptosis through upregulation of beclin-1, microtubule-associated proteins 1A/1B light chain 3 (LC3), and cleaved caspase-3, and downregulation of Bcl-2 in SGC7901 gastric cancer cells [ 150 ]. Furthermore, fucoxanthin activated apoptosis via inhibition of PI3K/Akt/mTOR pathway in U87 and U251 human glioma cancer cells [ 151 ] and induced apoptosis in adenocarcinoma SGC-7901 or BGC-823 human gastric cells involving downregulation of Mcl-1, STAT3 and p-STAT3 [ 152 ].…”
Section: The Use Of Carotenoids In Preclinical Cancer Researchmentioning
confidence: 99%